Political appointments to rector positions: a shifting landscape in Turkish academia - Ceyhun Elgin (Springer, 2024)
Abstract This paper examines the shifting landscape of higher education in Turkey, highlighting a disconcerting trend of politically motivated appointments, coined as "parasailing." Departing from traditional merit-based norms, this practice of appointing professors without necessary approvals disrupts the academic environment, prompting concerns about the integrity of higher education institutions. The paper introduces the term "parasailing" to elucidate this phenomenon, emphasizing the connection between the appointed professor and their academic destination. In contrast to the widely used term "parachuting," in Turkish academia the proposed terminology offers a better understanding of the appointment process. The subsequent sections provide an overview of the Turkish academic landscape, explore the origin of the term "parachuting," review existing literature, define "parasailing," and connect it to different philosophical thoughts. Overall, this paper contributes to a broader comprehension of the challenges facing Turkish higher education, urging a reconsideration of appointment procedures.